2012
DOI: 10.1002/ar.22444
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Juxta‐Oral Organ in Rat Embryo

Abstract: The aim of this work is to clarify the development and morphology of the juxta-oral organ (JOO) in rat embryos from Day (E)14 to 19. Furthermore, in the region of the JOO, an analysis was made of the expression of the monoclonal antibody HNK-1, which recognizes cranial neural-crest cells. In this study, we report that JOO develops from an epithelial condensation at the end of the transverse groove of the primitive mouth at E14. During E15, it invaginates and is disconnected from the oral epithelium. At E16, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The importance of the JOO stroma during development has been reported previously. In rats, there is evidence that it is derived from the neural crest (Velasco et al, 2012). Furthermore, it has also been suggested that the melanin pigmentation identified within the JOO stroma in human adults is produced by melanocytes derived from the neural crest (Ide et al, 2003).…”
Section: References Species Positive Immunostaining Negative Immunost...mentioning
confidence: 99%
“…The importance of the JOO stroma during development has been reported previously. In rats, there is evidence that it is derived from the neural crest (Velasco et al, 2012). Furthermore, it has also been suggested that the melanin pigmentation identified within the JOO stroma in human adults is produced by melanocytes derived from the neural crest (Ide et al, 2003).…”
Section: References Species Positive Immunostaining Negative Immunost...mentioning
confidence: 99%